Shoulder Functional Performance Status of National Collegiate Athletic Association Swimmers: Baseline Kerlan-Jobe Orthopedic Clinic Scores. (June 2015) - Wymore, Lucas; Fronek, Jan
Background: Shoulder trouble, described in the literature as "swimmer's shoulder, " has been associated with competitive swimmers. The Kerlan-Jobe Orthopedic Clinic (KJOC) Shoulder and Elbow Score is a validated survey used to define functional and performance measures of the upper extremity in overhead athletes. To date, no study has investigated the baseline functional scores for swimmers actively competing in the sport. Purpose: To establish a baseline score for National Collegiate Athletic Association (NCAA) swimmers actively competing in the sport. Study Design: Cross-sectional study; Level of evidence, 3. Methods: After institutional review board approval, the KJOC Shoulder and Elbow Score was administered to 5 NCAA swim teams (N = 99 participants; 46 men, 53 women). The results on 10 specific individual questions and on the total score were calculated according to the survey's original description. The mean scores were calculated for all participants. The Mann-Whitney U test was used to determine differences between sexes, years swimming, and self-reported injury status. Results: The mean ± SD baseline KJOC score (out of a possible 100) for all participants was 79.0 ± 18.7; the mean score for men was 81.9 ± 15.6 and for women 76.6 ± 20.8. The score for athletes identifying themselves as injured at baseline was 53.9 ± 18.8, compared with 84.4 ± 13.6 for those not reporting as injured ( P < .001). Athletes competing ≥11 years had a mean score of 72.0 ± 22.1; those competing ≤10 years scored 86.4 ± 11.4 ( P = .007). Conclusion: Baseline scores for swimmers, which were lower than expected, were lower than baseline scores seen in studies of other overhead sports athletes. The data corroborate previous studies identifying swimmers as having a high level of shoulder trouble. Further research is indicated for improving shoulder symptoms and performance in competitive swimmers.